Autoantibodies and Resident Renal Cells in the Pathogenesis of Lupus Nephritis: Getting to Know the Unknown - Susan Yung; Tak Mao Chan (Clinical and Developmental Immunology)
Systemic lupus erythematosus is characterized by a breakdown of self-tolerance and production of autoantibodies. Kidney involvement (i.e., lupus nephritis) is both common and severe and can result in permanent damage within the glomerular, vascular, and tubulo-interstitial compartments of the kidney, leading to acute or chronic renal failure. Accumulating evidence shows that anti-dsDNA antibodies play a critical role in the pathogenesis of lupus nephritis through their binding to cell surface proteins of resident kidney cells, thereby triggering the downstream activation of signaling pathways and the release of mediators of inflammation and fibrosis. This paper describes the mechanisms through which autoantibodies interact with resident renal cells and how this interaction plays a part in disease pathogenesis that ultimately leads to structural and functional alterations in lupus nephritis.